From Plowshares to Swords: The American Economy in World War II - Hugh Rockoff (Rutgers University, Department of Economics, 1994)
This paper examines the U.S. Economy in World War II. It argues that the mobilization must be viewed as a rapidly evolving historical process rather than, as is often the case, a single differentiated event. For example, the employment of unemployed resources, a factor often cited to explain the success of the mobilization, was important during the national defense period, but was relatively unimportant during the period of active U.S. involvement. The paper also discusses the limitations of the basic time series.
Keywords: N1; N4; 330; controls; world war II